Ecological Study of Fungi Isolated from the Surface Water of Dudhawa Dam Dhamtari, Chhattisgarh, India - Parveen2, K. Sharma1*; Shaista (Journal of Phytology, 2011)
Dudhawa Dam is located in Dhamtari district of Chhattisgarh in India. It is built across Mahanadi river in Dudhawa villag. The quantitative and qualitative fungal composition of dam water was surveyed monthly for a year i.e. March 2010 to February 2011. A variety of fungal strains was isolated and identified from the water of Dam. Out of a total 193 fungal colonies, 35 fungal species belongs to 16 fungal genera were isolated. Aspergillus niger was most frequent species with 91.67%, Neoarachnotheca keratinophila (75%) followed by A. flavus and A. fumigatus with 66.67% frequency. It was also found that maximum percentage contribution was observed for Aspergillus fumigatus (19.68%), which was followed by Aspergillus niger with (18.65% ) contribution.